A novel UPLC‐MS/MS method for simultaneous determination of 10 effective constituents in the Jixingshizhen preparation. (20th October 2016) - Cui, Kunna; Sun, Shuo; Wang, Ping; Luo, Linda; Yu, Jia; Guo, Xingjie
Abstract : A novel, reliable and reproducible UPLC‐MS/MS method was developed and validated to determine simultaneously the 10 bioactive constituents (baicalin, baicalein, wogonoside, wogonin, luteoloside, dictamnine, fraxinellone, obacunone, geniposidic acid and glycyrrhizic acid) in Jixingshizhen (JXSZ) preparation. Briefly, chromatographic separation was achieved on a Waters BEH C18 column with gradient elution employing a mobile phase composed of acetonitrile and 0.1% formic acid at a flow rate of 0.3 mL/min. All analytes containing internal standard (verapamil) were detected without interference in the multiple reaction monitoring mode with positive electrospray ionization. Further, a comprehensive validation of the method was rigorously executed according to the guidelines of the International Conference on Harmonization and Chinese Pharmacopoeia (2015 Edition). The results indicated that the validated method afforded desired linearity, precision, accuracy, sensitivity and stability. At length, the newly established method was successfully applied to quantify the 10 effective ingredients in JXSZ granules from different production batches, indicating the proposed method in this paper was particularly preferable for the routine analysis of JXSZ preparation as well as the quality control, particularly in situations where high sample throughput and fast analytical speed are required.